Kematian Akibat Prolonged Hipoksia pada Status Epileptikus - Agustiawan Imron; Feby Purnama (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Status epilepticus (SE) is a condition that results from the failure of the mechanisms responsible for seizure cessation or from the initiation of mechanisms, leading to prolonged seizures. This is a condition that can have long-term effects (especially if the duration is >30 minutes) such as death, injury, and changes in neuronal tissue depending on the type and duration of the seizure. The human brain consumes a very disproportionate amount of energy given its relatively small size, thus requiring a system capable of balancing cellular oxygen metabolism and brain blood flow control in order to maintain brain oxygen levels. Seizures have been shown to cause changes in oxygen levels beyond the normoxic range, which increases the likelihood that seizure-induced changes in brain pO2 may affect brain function during and after seizures. Decreased oxygenation is common during epileptic seizures. This has been seen on digital pulse oximetry (which measures oxygenation of either the fingers or toes) in the 25-33% saturation range when they have seizures. Such hypoxemia is more common in seizures that are generalized (ie begin as or become generalized tonic-clonic seizures) and/or prolonged.